2019
DOI: 10.1016/j.neuron.2019.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Low-Threshold Spiking Interneurons Regulate Goal-Directed Learning

Abstract: Highlights d Striatal low-threshold spiking interneurons (LTSIs) mediate goal-directed learning d Reward-associated LTSI Ca 2+ activity decreases with operant learning d Decreasing LTSI activity accelerates and increasing LTSI activity slows learning d Effects on learning are dependent on LTSI GABAergic signaling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 50 publications
4
68
0
Order By: Relevance
“…In support of this, elimination of CINs in the DMS was shown to enhance behavioral flexibility 74 , while the destruction of thalamic afferents to DMS produced a deficit in goal-directed learning 34 . These studies suggest that thalamic afferents may modulate certain behavioral functions in the DMS through the connectivity with other striatal interneurons 75 , such as the low-threshold spiking interneurons, which were recently found to modulate the acquisition of novel contingencies in a goal-directed task 76 . Such a central role of LDT afferents in the modulation of goal-directed behavior is in agreement with recent evidence supporting its role in reinforcement learning through the modulation of dopamine neurons 19,20,77 .…”
Section: Discussionmentioning
confidence: 87%
“…In support of this, elimination of CINs in the DMS was shown to enhance behavioral flexibility 74 , while the destruction of thalamic afferents to DMS produced a deficit in goal-directed learning 34 . These studies suggest that thalamic afferents may modulate certain behavioral functions in the DMS through the connectivity with other striatal interneurons 75 , such as the low-threshold spiking interneurons, which were recently found to modulate the acquisition of novel contingencies in a goal-directed task 76 . Such a central role of LDT afferents in the modulation of goal-directed behavior is in agreement with recent evidence supporting its role in reinforcement learning through the modulation of dopamine neurons 19,20,77 .…”
Section: Discussionmentioning
confidence: 87%
“…Sharott and colleagues described that in vivo , NOS + interneurons exhibit very low spontaneous firing and are preferentially activated by phasic responses (Sharott, Doig, Mallet, & Magill, ). It was also recently shown that striatal SSTi serve to negatively regulate the rate of goal‐directed task learning (Holly et al., ); however, the chronic ablation of these neurons in our model may have precluded identifying this kind of deficit. On the other hand, it cannot be ruled out that after spending longer periods in the absence of SSTi, changes in the locomotor, emotional or pain sensitivity parameters would take place.…”
Section: Discussionmentioning
confidence: 85%
“…MSNs also interact via lateral inhibitory connections (Burke, Rotstein, & Alvarez, ; Plenz, ). Studies have shown a role for parvalbumin‐positive fast spiking interneurons (FSIs), cholinergic interneurons, and low threshold spiking interneurons in movement and/or associative learning (Brown et al, ; Gittis, Leventhal, et al, ; Gritton et al, ; Holly et al, ; Lee, Finkelstein, Choi, & Witten, ; Lee et al, ; O'Hare et al, ; Owen, Berke, & Kreitzer, ). The function of other interneuron types, as well as MSN lateral inhibition, is less well understood.…”
Section: Overview Of Striatal Functionmentioning
confidence: 99%